1982
DOI: 10.1203/00006450-198210000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Group B Streptococcal Colonization with Topically Applied Lipoteichoic Acid in a Maternal-Newborn Mouse Model

Abstract: SummaryAn animal model of maternal-newborn transmission of group B streptococci (GBS) was developed. Pregnant Swiss-Webster mice were colonized by applying 10' GBS to the oral cavity, vagina, and nipples daily for 3 days before delivery. Lipoteichoic acid (LTA) from type 111 GBS or phosphate buffered saline was applied topically to the oral cavity, perineum or nape of newborn mice.Cultures of newborn mice at 3 days of age revealed 35 of 75 (47%) controls and 0 of 79 animals given 2 doses of LTA (2 mg/ ml) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…A recent report showed that free LTA specifically blocks intracellular invasion of Hep2 pharyngeal epithelial cells by S. pyogenes without affecting overall cellular adherence (44). In vivo, topical administration of LTA has also been shown to be effective in blocking vaginal colonization of pregnant mice by GBS (45). Our findings in invasion assays performed in the presence of ∆iagA supernatants containing high levels of released LTA appear to support these earlier observations.…”
Section: Figuresupporting
confidence: 81%
“…A recent report showed that free LTA specifically blocks intracellular invasion of Hep2 pharyngeal epithelial cells by S. pyogenes without affecting overall cellular adherence (44). In vivo, topical administration of LTA has also been shown to be effective in blocking vaginal colonization of pregnant mice by GBS (45). Our findings in invasion assays performed in the presence of ∆iagA supernatants containing high levels of released LTA appear to support these earlier observations.…”
Section: Figuresupporting
confidence: 81%
“…In a previous study, topical oral and cutaneous application of LTA to newborn mice was nontoxic and com~letelv re vented GBS colonization of neonates by their vaginall;colok~ed mothers (5). Topical application of LTA to human neonates may also prevent GBS colonization after contact with maternal mucosal and skin surfaces at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Four hours after intradermal injection, LTA from group A streptococci was found in the cortical tubular regions closely associated with glomeruli, but glomeruli themselves showed little LTA deposition (17). The absence of oral absorption of LTA may be due to its rapid adherence to and slow elution from cell membranes (5,28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attachment is mediated by lipoteichoic acid (LTA) [4,11,12] on the surface of GBS. Receptor sites for GBS on neonatal cell surfaces may differ from those on adult cells [11] and explain, in part, the increased susceptibility of newborn infants to GBS disease.…”
Section: Introductionmentioning
confidence: 99%